Corporate governance, board practices and performance of shipping firms in Bangladesh - Wahidul Sheikh; Khairul Alom (Asian Journal of Shipping and Logistics (AJSL), 2021)
This study attempts to take a close look on corporate governance, board practices and performance of shipping firms in Bangladesh. The study has conducted a survey on 24- shipping firms operated in Bangladesh and collected perceptional data from top tier executives and factual data from firms balance sheet and income statement. The results of descriptive statistics show that most of the firms' managers are not aware about the corporate governance and board practices of the firm. Moreover, there is significant lack of transparency in the board practices documented among the shipping firms in this study. The results of regression analysis confirm that board ownership, board leadership, board size, and firm size have significant impact on firm performance. Moreover, factual analysis results show that board leadership has significant impact on firm performance. However, this study also confirmed that board composition has no significant impact on firm performance in the context of Bangladeshi shipping firms. Thus, this is of the essence to spotlight on corporate governance policies in the shipping firms to make legal aspects of board practices to escalate the growth of shipping industry in Bangladesh.
Keywords: C58; C83; G34; 650; Corporate governance; Board ownership; Board composition; Board leadership; Firm performance